DEVELOPING MODULE OF CHILDREN LITERATURE TO INCREASE THE STUDENTS' CRITICAL THINKING - Fikri, Hajarudin Al; Zubaidah, Enny (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2019)
Abstract: This study aimed to (1) produce a module of children literature based on nationalism character to improve the critical thinking ability of the fourth grade students of MIN Boyolali, and (2) measure the effectiveness of the module used in classroom toward critical thinking ability of the fourth grade students of MIN Boyolali. Set within the research and development type, this study adapted the development procedure formulated by Borg and Gall (1983). Data were collected through interview and observation, product validation, questionnaire of the teacher and the students’ response, and the result of pre-test and post-test which was analyzed using independent sample t-test. Meanwhile, the effectiveness was tested through quasi experiment. The result of the research showed that the module was categorized as “fit” by material and language expert; while the media expert categorized it as "very fit". In the other hand, the teacher and the students’ responses to the use of learning module were categorized as "excellent". Further, the output of the independent sample t test showed that the module was effective to improve the students' critical thinking skills. Abstrak: Penelitian ini bertujuan untuk (1) menghasilkan modul sastra anak berdasarkan karakter nasionalisme untuk meningkatkan kemampuan berpikir kritis siswa kelas IV MIN Boyolali, dan (2) mengukur efektivitas modul yang digunakan di kelas terhadap kemampuan berpikir kritis siswa kelas IV MIN Boyolali. Penelitian ini adalah jenis penelitian pengembangan yang mengadaptasi prosedur pengembangan yang dirumuskan oleh Borg dan Gall (1983). Data dikumpulkan melalui wawancara dan observasi, validasi produk, kuesioner dari guru dan respon siswa, dan hasil pre-test dan post-test yang dianalisis menggunakan independent sample t-test. Sementara itu, keefektifannya diuji melalui eksperimen semu. Hasil penelitian menunjukkan bahwa modul dikategorikan “cocok” oleh ahli materi dan bahasa; sedangkan pakar media mengategorikannya "sangat pas". Di sisi lain, respons guru dan siswa terhadap penggunaan modul pembelajaran dikategorikan "sangat baik". Selanjutnya, hasil dari uji t sampel independen menunjukkan bahwa modul ini efektif untuk meningkatkan keterampilan berpikir kritis siswa